Effectiveness of Digital Payment from the Perspective of Generation-Z and Millennial E-commerce Consumers: MSME Resilience in West Java - Fajri, Hanan Zaidane Noor; Delia, Irene; Elizabeth, Irene (PT Literasi Nusantara Publisher, 2025)
The ease of transactions in purchasing products significantly influences Generation Z (aged 8 to 23) and millennial (aged 24 to 39) buyers in e-commerce. The adoption rate of digital payments is high, reaching 95%, with 75% of users expecting to increase their usage in the next one to two years (SEA e-Conomy Research Survey, 2021). This study examines the impact of digital payments on buyer satisfaction and MSME resilience using a quantitative approach and Partial Least Square (PLS) analysis. The research data used in this study was collected in 2023. Drawing on the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Mental Accounting Theory (MAT), this research integrates transaction security, individual influences, and data protection as key factors. Through a survey of 77 Generation-Z and 73 millennial respondents, findings reveal that social influence, ease of use, and trust significantly shape security perceptions. This study provides insights into enhancing digital payment quality and offers policy recommendations for improving MSME sustainability.